Archaeological Practice as Politics and Ethics - Carman, John. author. aut Link
XVII, 197 p.
Keywords: This book is of relevance to all archaeologists and all others concerned with how an interest in the past impacts on the present. This book explores the manner in which archaeology as a discipline and a field of endeavour contributes to the modern world. The focus throughout the book is on practices - the range of different things that archaeologists do and how they do and have done it in order to explore the field as a distinctive aspect of social practice over time. It also concerns the structures – social, political, economic, professional, philosophical – in which archaeology is performed and the consequences for the discipline and its practitioners. Throughout there is a concern especially with archaeology as a field of political and ethical decision-making, aspects well recognised by practitioners but rarely emphasised. The book both asks and answers questions about the perception of archaeology from both within and outside the field. The book draws widely on previous work by the author and others – looking at the techniques of the field, the people involved, the political and social impacts both on and by the field. In doing so it seeks to bring these different perspectives together to create a more holistic idea of what archaeology is, has been, and could be. The book is offered to those outside the field as a justification for archaeology – a field coming under increasing pressure from those who consider it (as so many humanities and social science disciplines) as an expensive luxury.